3D-Printed Hand Splints versus Thermoplastic Splints: A Randomized Controlled Pilot Feasibility Trial - Waldburger, Leonie; Schaller, Romain; Furthmüller, Christina; Schrepfer, Lorena; J. Schaefer, Dirk; Kaempfen, Alexandre (International journal of bioprinting, 2022)
In this randomized controlled pilot trial, we compared three-dimensional (3D)-printed made-to-measure splints to conventional custom-made thermoplastic splints. In a clinical setting, we evaluated their general applicability and possible benefits for immobilization in hand surgical patients. We included 20 patients with an indication for immobilization of at least 4 weeks, regardless of the splint design. Patient comfort and satisfaction were assessed with questionnaires at splint fitting, as well as 2 and 4-6 weeks later. The 3D splints were designed and printed in-house with polylactic acid from a 3D surface scan. Our data suggest that 3D-printed splinting is feasible, and patient satisfaction ratings were similar for 3D-printed and thermoplastic splints. The 3D splint production process needs to be optimized and other materials need to be tested before routine implementation is possible or more patients can be enrolled in further studies. Validated quality assessment tools for current splinting are lacking, and further investigation is necessary